Plant Reproduction - Plant Reproduction (Springer Nature, 2026)
Plant Reproduction is a journal devoted to publishing high-quality research in the field of reproductive processes in plants. Article formats include original articles, short communications, reviews, perspectives, method papers, and opinion papers.
FI 0.79
Q2
Keywords: Life Sciences; Cell & Molecular Biology; Biología celular; Biología molecular; Acuerdos transformativos; Transformative agreements; Reproducción vegetal; Genética; Bioquímica